PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA MUMTAAZ BAKERY SANGATTA - Rizky Aulia Hidayah (Tinta Nusantara 2018 Vol.1, 2022)
The purpose of this study was to determine how big the influence of service quality on customer satisfaction at Mumtaaz Bakery Sangatta. The research method uses quantitative methods and uses a questionnaire to a sample of 96 respondents. The analytical tool used is simple linear regression with the help of the SPSS 21 program. The results obtained from data processing are known that the R value is 0.666. This shows that service quality (X) has a strong relationship, while the coefficient of determination (R2) is 0.444, which means that service quality (X) affects customer satisfaction (Y) by 44.4%, while the rest is 55.6. % is influenced by other variables not examined. The conclusion of this study as a whole is that service quality has a positive and significant effect on customer satisfaction at Mumtaaz Bakery Sangatta